Physical modeling of local scour around wide and skewed piers - Ahmad, Nordila (2015)
Local scour around bridge piers has been recognised as one of the major causes of bridge failure. Since the 1950s numerous studies on local scour around bridge foundations have been conducted, however the problems of scour prediction have still not been totally overcome due to the difficulties in understanding the mechanism of scour and the complexity of flow around bridge piers. The aim of this study is to investigate the temporal development, effect of sediment coarseness,and pier geometry around wide and long skewed piers with multiple sizes and shapes in a bed formed with the use of two different sizes of sediments. In this study and for wide pier analysis, ten piers with circular and rectangular shapes were tested. Furthermore, one rectangular pier was chosen for inclusion in an experiment on skewed piers at various angles of attack, . Scour development was monitored during the initial stage, main erosion stage, and equilibrium stage around wide and skewed piers. A new relationship of scour prediction based on laboratory and field data is proposed for the purpose of improving scour prediction techniques that have a tendency to overpredict local scour depths for wide piers. Validation of the proposed scour prediction formula was conducted using a wide range of laboratory and field data. Statistical tests revealed that application of the proposed scour prediction formula produced the smallest discrepancy ratio and root mean square error value among the tested models and showed good agreement with existing scour prediction formulae. The effects of wide piers and long skewed piers on the geometry of scour holes and sediment ridges (sediment deposited at downstream near the scour holes) were also explored. The tests were performed with the pier Reynolds number (Rep) within the range of 2.2x104 ≤ Rep ≤ 2.1x105. The present experimental evidence shows that the geometric characteristics of scour holes and sediment ridges (length and width) were decreases as pier Reynolds number Rep increases. The trend of empirical relations demonstrates the effects of the studied variables, including angle of attack, on scouring and deposition volumes at different sediment sizes. It also shows that the scouring volume is much higher than the sediment ridge volume that give indication that suspended sediment transport becomes more significant as the skewness of a long pier increases. A new relationship for estimating the angle of attack factor, K, for shallow-water conditions is presented. The new method of estimating Kwas compared with HEC- 18 and Laursen’s and Toch’s curves and the superiority of the new method was verified using statistical analyses.